What should be subtracted from the product of (x-3) (x2 + 3x + 9) to get
+ 3x +9.
Answers
Answered by
0
(x-3)(x²+3x+9)
=> x³-3³ = x³-27
=> (x³-27)-P(x) = x³-3x+9
=> P(x) = 3x - 36
3x - 36 Should be Substituting From x³-7
To get,
=> x³-3x+9
- I Hope it's Helpful.
Answered by
0
Answer:
this is the answers
Step-by-step explanation:
please mark as brain liest
Attachments:
![](https://hi-static.z-dn.net/files/d2a/ca1236e1b7d01aafab80900ff8150047.jpg)
Similar questions
Social Sciences,
3 months ago
English,
3 months ago
Social Sciences,
3 months ago
Math,
1 year ago
Math,
1 year ago